3D radiation, density, and MHD structures following neon shattered pellet injection into stable DIII-D Super H-mode discharges. (28th May 2021) - Sweeney, R.; Baylor, L.R.; Eidietis, N.W.; Granetz, R.S.; Herfindal, J.L.; Hollmann, E.M.; Hu, D.; Lehnen, M.; Moyer, R.; Raman, R.; Shiraki, D.; Strait, E.J.; et al.
Abstract: Six nominally repeat neon shattered pellet injection (SPI) shutdowns of stable DIII-D Super H-modes are studied to understand the 3D properties of the radiation and impurity transport. The radiation efficiency and radiation peaking determine whether first wall melting is expected following disruption mitigation in ITER. Previous studies make use of axisymmetric approximations to infer radiation efficiencies, but validating the high efficiency required by ITER necessitates improved accuracy, and this work contributes by exploring the 3D radiation and density structures that will inform forward modeling. When the neon shatter plume produced by the SPI reaches the plasma edge, m / n = 3/1 and 2/1 island O-points are observed to align with the injection trajectory in five out of six cases, suggesting that the injected material seeds the island O-points. Field aligned neon structures emitting Ne-I line radiation drift at 1 km s −1 in the ion diamagnetic drift direction during the pre-thermal quench, tracking the motion of the m / n = 2/1 island O-point. Neon fragments penetrate to the q = 2 surface by the time of the thermal quench. Techniques to constrain the 3D emissivity are explored, and one method constrains a 3D flux tube that is consistent with the radiation data, and when mapped to the interferometers, intersects the lasers that measure the highest density. The resulting structure derived from the radiation measurements exists near the 2/1 island X-point. In five repeatable discharges, the peak of the radiation in the toroidal direction exists in a 120° toroidal sector where the injection occurs, in contrast with the outlier discharge where the toroidal peak exists in the complementary 240° toroidal sector far from the injector, and where a 50% lower density rise is observed. The n = 1 phase behavior is markedly different in the outlier discharge, suggesting a possible dependence of the radiation structure and the assimilation efficiency on MHD.